Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1099/mic.0.069930-0
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur oxidation to sulfate coupled with electron transfer to electrodes by Desulfuromonas strain TZ1

Abstract: Microbial oxidation of elemental sulfur with an electrode serving as the electron acceptor is of interest because this may play an important role in the recovery of electrons from sulfidic wastes and for current production in marine benthic microbial fuel cells. Enrichments initiated with a marine sediment inoculum, with elemental sulfur as the electron donor and a positively poised (+300 mV versus Ag/AgCl) anode as the electron acceptor, yielded an anode biofilm with a diversity of micro-organisms, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 41 publications
0
31
0
1
Order By: Relevance
“…The presence of the Desulfuromonas genus was not surprising, as these bacteria had already been identified as electroactive in the pioneering MFC studies. [43] This genus has been found to be dominant on bioanodes formed from marine sediments [44,45] and other different types of inoculum, such as paper-mill effluents. [46] Desulfuromonas acetoxidans is known to reduce Fe III oxides through outer-membrane type-C cytochromes [47] and it has been implemented in MFCs.…”
Section: Microbial Communities On Bioanodesmentioning
confidence: 99%
“…The presence of the Desulfuromonas genus was not surprising, as these bacteria had already been identified as electroactive in the pioneering MFC studies. [43] This genus has been found to be dominant on bioanodes formed from marine sediments [44,45] and other different types of inoculum, such as paper-mill effluents. [46] Desulfuromonas acetoxidans is known to reduce Fe III oxides through outer-membrane type-C cytochromes [47] and it has been implemented in MFCs.…”
Section: Microbial Communities On Bioanodesmentioning
confidence: 99%
“…Recently it was shown that Desulfuromonas species are capable to S° oxidation coupled to electron transfer to electrodes which has important implications for the interpretation of the function of microbial communities colonizing anodes and harvesting electricity from marine sediments 10 . Desulfuromonas species are often the most abundant species in the biofilms of marine sediment fuel cells 10,[22][23][24][25] . It was previously assumed that the primary role of these organisms was the oxidation of acetate coupled to current production.…”
Section: The Prospects Of D Acetoxidans Imv B-7384 Application Whilementioning
confidence: 99%
“…However, by setting the anode potential at +300 mV vs. Ag/AgCl, the abstraction of electrons from sulfur by sulfur-oxidizing species forms sulfate that can be reduced again to H2S by sulfate-reducing microorganisms, such as Desulfovibrio species that belong to sulfur cycle bacteria 10 . Recently it was shown that Desulfuromonas species are capable to S° oxidation coupled to electron transfer to electrodes which has important implications for the interpretation of the function of microbial communities colonizing anodes and harvesting electricity from marine sediments 10 . Desulfuromonas species are often the most abundant species in the biofilms of marine sediment fuel cells 10,[22][23][24][25] .…”
Section: The Prospects Of D Acetoxidans Imv B-7384 Application Whilementioning
confidence: 99%
See 1 more Smart Citation
“…Since the electron transfer mechanisms so far observed in BESs resemble closely to the mechanisms investigated for dissimilatory metal reducing microorganisms 4 , D. acetoxidans is very promising anode biocatalyst for MFC that is not investigated enough presently. Recently it was shown that despite hydrogen sulfide generation as a result of S 0 -reduction, this bacterium can also oxidize elemental sulfur to sulfite and sulfate with an electrode serving as the electron acceptor 9 . Since sulfur can accumulate on anodes from the abiotic oxidation of sulfide it shows the possibility of continuous simultaneous carrying of opposite stages of sulfur cycle in the anode chamber of MFC by activity of only one genus of bacterium.…”
Section: Introductionmentioning
confidence: 99%